Influence of electrolytic-plasma surface quenching on the structure and strength properties of ferritic-pearlite class wheel steel - Rakhadilov, B; Tabiyeva, Y. Y.; Uazyrkhanova, G. K.; Zhurerova, L. G.; Baizhan, D. (Eurasian Journal of Physics and Functional Materials, 2026)
This paper examines the influence of electrolyte-plasma surface hardening on the structure and micro hardness of wheel steel mark 2. In the work electrolyte-plasma surface quenching was carried out in an electrolyte made from an aqueous solution of 10% carbamide (NH 2 ) 2 CO+20% sodium carbon ate Na 2 CO 3 . The work investigated the strength limit, fluidity and wear intensity of the wheeled steel after electrolyte-plasma surface quenching. After electrolytic-plasma surface quenching, a batch, high-temperature plate and low-temperature plate martensit is formed on the surface of the sample. Investigations have been carried out on microhardness determination on cross-section of wheel steel sam ples after quenching in aqueous solution of electrolyte. It is found that after electrolytic-plasma surface quenching, the microhardening values of this hardened surface layer increased on ≈ 3 times compared to the steel matrix, and the thickness of the hardened layer is 1000-1500 µm. According to the results of the scanning transmission electron microscopy, the electrolyte-plasma surface quenching caused a change in the morphological constituents of steel mark 2. In the initial state, the matrix of steel is a α -phase, the morphological components of which are fragmented ferrite, unfragmented ferrite and pearlite. Recommended Citation Rakhadilov, B. K.; Tabiyeva, Y. Y.; Uazyrkhanova, G. K.; Zhurerova, L. G.; and Baizhan, D. (2020) "Influence of electrolytic-plasma surface quenching on the structure and strength properties of ferritic-pearlite class wheel steel," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 2, Article 8. DOI: https://doi.org/10.29317/ejpfm.2020040208